Repurposing of Angiotensin-converting-enzyme Inhibitor on Prevention of Post-surgical Tendon Adhesion - Naimi, Hamideh; Khazaei, Majid; Sharifnia, Fariba; Sayyed-Hosseinian, Sayyed-Hadi (Current Pharmaceutical Design, 2024)
Background: Formation of adhesion bands is a frequent clinical complication after tendon injury or surgery with limited treatment options. This study investigates the repurposing of Angiotensin-Converting-Enzyme Inhibitor (ACEI) in attenuating post-operative tendon-sheath adhesion bands in an Achilles tendon rat model. Methods: Structural, mechanical, histological, and biochemical characteristics of the Achilles tendons were compared in the presence and absence of oral ACEI (enalapril) using the Achilles tendon adhesion (TA) model in rats. Inflammation and total fibrosis of tendon tissues were compared between groups using molecular investigations along with macroscopic and histological scoring methods. Results: ACEI significantly alleviated the severity, length, and density of Achilles TAs. Moreover, histopathological changes, recruitment of inflammatory cells, and inflammation were significantly decreased in post-operative tissue samples as quantified with the Moran scoring model. We showed that ACEI treatment elicits a potent anti-fibrotic effect on tendon tissue samples, as illustrated by decreasing the severity and extent of the formed fibrotic tissue and collagen accumulation at the site of surgery when scored either by Tang or Ishiyama grading systems. The H staining showed no histopathological changes or damage to the principal organs. Conclusion: Our results showed that ACEI is a safe and effective therapeutic candidate with potent immunomodulatory and anti-fibrotic features to alleviate surgery-induced development of fibrotic adhesive tissue. However, its efficacy needs to be further validated in clinical studies.
Keywords: post-surgical tendon adhesion